(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To investigate the applicability of current hematological reference intervals in interpreting selected blood cell parameters among pregnant women at Hung Yen Obstetrics and Pediatrics Hospital. Subjects and methods: A cross-sectional descriptive study was conducted using retrospective data from 1,376 pregnant women with available gestational-stage information and results for RBC, HGB, WBC, and PLT. Applicability was assessed using the proportion of results outside the current reference intervals, the proportion of discrepant classifications between current and gestational stage-specific reference intervals, and the proportion of results outside the current intervals but within the gestational stage-specific intervals. Results: The highest proportions of results outside the current reference intervals were observed for HGB and WBC, at 72.3% and 63.1%, respectively, compared with 26.7% for RBC and 4.9% for PLT. Discrepant classification rates were also highest for HGB and WBC, at 70.9% and 62.7%, respectively. Conclusion: The applicability of current reference intervals varied across hematological parameters. HGB and WBC should be prioritized for verification or establishment of gestational stage-specific reference intervals.